The Knowledge and Attitude of Parents About the Dental Treatment of Their Children During the New Type of Coronavirus Outbreak in Northern Cyprus - Ekinci, Ayse; Tosun, Ozgur; Islam, Aylin (Frontiers in Public Health, 2022)
Objective: This study aimed to assess the knowledge and attitude of parents living in Northern Cyprus about dental treatment of their children during the COVID-19 outbreak. Method: An online self-administered questionnaire was conducted which consisted of 33 questions. A total of 256 parents participated in this study. The questionnaire was divided into two parts. The first part consists of demographic information and the second part consists of awareness and knowledge of parents about dental treatment during COVID-19. Results: The majority of the participants (77%) stated that their children may get infected with COVID-19 during dental treatment and were apprehensive about their children undergoing dental treatment because of the outbreak, but 65.1% did not take any extra precautions regarding their children's oral health and care. Conclusion: The majority of the parents had good knowledge about that dental clinics are one of the high-risk group areas where COVID-19 can be transmitted by aerosols from infected people. More studies are needed to assess the continuing impact of the COVID-19 pandemic on parents’ attitudes toward and knowledge about dental procedures.